The Visual Complexity = Higher Production Cost Lay Belief - Min, Lauren; Liu, Peggy J; Anderson, Cary L (Journal of Consumer Research, 2025)
Abstract Brands and retailers often offer different aesthetic versions of the same base product, which vary from visually simple to visually complex. How should managers price these different aesthetic versions of the same base product? This research provides insights for such decisions through uncovering a novel consumer lay belief about the relationship between visual complexity and production costs. Consumers associate simple (vs. complex) visual aesthetics with lower production costs when evaluating different aesthetic versions of a product. This lay belief occurs in joint evaluation mode but is mitigated in separate evaluation mode. An important downstream implication of this lay belief is that consumers’ willingness to pay is lower for visually simple (vs. complex) versions. This gap in willingness to pay occurs even when consumers like both product versions or aesthetics equally, and it is only eliminated when consumers like the visually simple version substantially more than the complex version. Finally, reducing the diagnosticity of the lay belief by disclosing information that the two versions took similar amounts of production time and effort reduces the gap in willingness to pay between visually simple (vs. complex) versions.